Research on Evaluation Index System for Power Market in China. Issue 4 (May 2019) - Su, Yang; Li, Ma; Menghua, Fan; Yanyuan, Qu; Zechen, Wu; Xiaoxuan, Zhang
Abstract: Since the 9th document issued by the Government, China's power market construction process speeds up. It is necessary to build a quantitative electricity market analysis and evaluation tool for power market design, operation, supervision and decision-making of market participants. This paper studies the tools and methods of electric power market evaluation under the situation of electricity system reform in China, and takes the influence on power industry development and various related groups into account. The main evaluation indexes include promoting the optimal allocation of resources, promoting the sustainable development of power industry, market efficiency, and orderly operation of the market, impact on related groups.